Reproductive efficiency of ewe lambs kept on tropical pastures under different feeding systems - L.M. Higano; C.C.B.F. Ítavo; L.C.V. Ítavo; G.S. Difante; G.K.A. Melo; P.C.G. Silva; K.L.S. Monteiro; E.S.M. Soares; T.F.F.S. Arco; P.B. Andrade; A.A.S. Miguel; F.G.G. Oliveira; et al. (Arquivo Brasileiro de Medicina Veterinária e Zootecnia)
ABSTRACT The aim of this study was to analyze the productive and reproductive performance of lambs submitted to different forms of feed supplementation in the growth phase and breeding season. Twenty-eight Texel sheep aged between three and 12 months were used. The lambs were distributed in two treatments with protein-energy supplementation at levels 1.6 and 2.4% of body weight and reared on Brachiaria brizantha cv. Marandu. The performance was evaluated at the beginning of the experimental period and every 28 days until the end of the breeding season, the following data were observed: final body weight, average daily gain (ADG) and total weight gain (TWG). In the growth period, the lambs supplemented with 2.4% BW presented higher average daily gain, which resulted in higher total weight gain and final weight. Thus, the ewe lambs supplemented with 2.4% BW showed greater subcutaneous fat thickness in the growth phase. However, during growth the lambs supplemented with 1.6% of BW showed better body condition score than those supplemented with 2.4% BW. There was no effect of supplementation on the size of the reproductive organs of the lambs at the end of the growth phase and at the beginning of the reproductive season. The supplementation levels used affected the pregnancy rate of the lambs. The group that received 1.6% BW had a higher pregnancy rate than the group treated with 2.4% BW. Thus, it is concluded that supplementation with 1.6% BW was economically viable to promote weight gain, body condition score, and stimulate fertility rate for primiparous lambs in a 45-day reproductive season.